2023
DOI: 10.1080/07853890.2023.2176542
|View full text |Cite
|
Sign up to set email alerts
|

The prediction value of platelet-derived growth factor for major adverse cardiovascular events in patients with acute non-ST-segment elevation myocardial infarction

Abstract: Background The value of plasma Platelet-Derived Growth Factor (PDGF) as a biomarker in predicting major adverse cardiovascular events (MACEs) in patients with acute non-ST-segment elevation myocardial infarction (NSTEMI) remains unclear. Methods A total of 242 patients with NSTEMI were enrolled in this observational cohort study. The correlation between PDGF and MACEs was evaluated during a five-year follow-up. Kaplan–Meier survival analysis with Cox proportional-hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
0
0
Order By: Relevance
“…This is also consistent with Sato et al [10] who investigated how the CADILLAC and GRACE risk ratings affected shortand long-term clinical outcomes in patients with acute myocardial infarction and found that 262 patients (32.4%) suffered from MACEs. However, our study is in contrast with Zhang et al [11] who studied if central arterial pressure predicts in-hospital MACEs after acute STEMI and revealed that MACEs occurred in 22.6% of patients. Also, Kumar et al [12] who studied the burden of short-term MACEs and its determinants after emergency PCI where MACEs were observed in 210 (19.1%) patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is also consistent with Sato et al [10] who investigated how the CADILLAC and GRACE risk ratings affected shortand long-term clinical outcomes in patients with acute myocardial infarction and found that 262 patients (32.4%) suffered from MACEs. However, our study is in contrast with Zhang et al [11] who studied if central arterial pressure predicts in-hospital MACEs after acute STEMI and revealed that MACEs occurred in 22.6% of patients. Also, Kumar et al [12] who studied the burden of short-term MACEs and its determinants after emergency PCI where MACEs were observed in 210 (19.1%) patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding angiographic data, Zhang et al [11] showed that low central systolic blood pressure group had the highest incidence of in-hospital complications. Similar to our result, Tesak et al [20] showed statistically significant higher LVEDP in non-survivors group (median= 30 mmHg, range 22-39 mmHg) when compared to survivors group (24 mmHg, range 12-38 mmHg) with p-value= 0.001 & with LVEDP was independent predictor for 30-day mortality [AUC 0.715, 95% CI (0.626; 0.803), p-value <0.001, cut-off value ≥20.5 mmHg].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed a weak correlation between MPV, PDW, eGFR, and wGRS as well as a positive correlation between the GRACE score and wGRS, particularly among patients with NSTEMI. Consistent with our study ndings, an observational cohort study of 242 NSTEMI patients followed up for a period of 5 years, observed a positive correlation between serum level of PDGF, and MPV and GRACE score [47].Coupled with the previously mentioned observations, this intimates a potential association among PDGF-related genetic effect, platelet attributes, and the severity of acute myocardial infarction gauged by the GRACE score. More comprehensive research is necessitated to delve deeper into the putative mechanisms and clinical implications of this connection.…”
Section: Discussionsupporting
confidence: 92%